Digital Transformation Maturity Analysis of Indonesian Navy Staff and Command College Using DTMM - Suharjo, Bambang; Rimbawa, H.A. Danang (Universitas Bina Darma, 2024)
The maturity of digital transformation refers to an organization’s development level in adopting and integrating digital technology into its business processes. The level of maturity of digital transformation in the Indonesian Navy Staff and Command College as a military education institution is very essential. The problem is the information on digital transformation maturity has not been obtained. The qualitative method through in-depth interviews was conducted on the leadership elements, namely the director and departmental heads to answer the question of digital transformation maturity. Interviews were developed in the policy and strategy, technology and infrastructure dimensions, the use of IT in the business process of educational institutions, IT-based learning, lecturers and education, data, digital leadership, efficiency and IT-based performance, and IT culture. Determination of maturity level was carried out using DTMM at initial, developing, defined, managed, and optimized. The results of the study show that overall, the level of maturity of digital transformation at the Naval Staff and Command School has reached a defined (systematic) level. The strategy for increasing the maturity of digital transformation at the Naval Staff and Command School needs to be continuously developed and implemented in each dimension.